Employee acceptance of disruptive service innovations at the frontline: The role of collective sensemaking processes - Christopher Garrelfs; Carsten Schultz; Marie Luengen (Creativity and Innovation Management, 2023)
Acceptance of service innovation by frontline employees is a challenging issue, especially if such innovations have the potential to disrupt existing value creation models and individual competencies. Disruptive service innovations are often (1) characterized by a high degree of innovativeness related to significant changes in technology and in the market and (2) may be introduced by technology manufacturers as new service market entrants that cause a competitive threat to the existing service provision. We argue that such innovations challenge frontline employees' focus on routines and standardized service operating procedures. The perceived threat and resulting high levels of uncertainty may inhibit innovation acceptance. Our study follows a collective sensemaking perspective, paying special attention to investigating the moderating role of (1) the exchange of operational information within a workgroup and (2) a firm's entrepreneurial orientation. Whereas the former may increase frontline employees' preference for incremental improvements, the latter may help to increase the acceptance level of potentially more disruptive innovations. We test our theoretically derived hypotheses with an experimental vignette study of 671 frontline employees in the field of audiology, a health care market particularly affected by both more radical and market entrant innovations. Results show that a high degree of innovativeness has a negative effect on innovation acceptance. Frontline employees accept radical innovations less readily than incremental innovations. A competitive threat from new technology manufacturers in the supply chain does not lead to a lower innovation acceptance level. The moderation results indicate significant effects of both information exchange and entrepreneurial orientation. Intensive information exchange within the workgroup strengthens the negative relationship between the degree of innovativeness and innovation acceptance. In contrast, a high degree of entrepreneurial orientation weakens the negative relationship between a competitive threat and innovation acceptance.
Keywords: 330; collective sensemaking; competitive threat; disruptive service innovation; frontline employees; health care; innovation acceptance; market entrant innovation